2016
DOI: 10.1002/dmrr.2841
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic nephropathy in type 1 diabetes: a review of early natural history, pathogenesis, and diagnosis

Abstract: Diabetic nephropathy constitutes a devastating complication in patients with type 1 diabetes mellitus, and its diagnosis is traditionally based on microalbuminuria. The aim of this review is to update through the medical literature the suggested early natural course of diabetic nephropathy, the theories behind the pathways of its pathogenesis, and its diagnosis. Poor glycemic control, dyslipidemia, smoking, advanced glycation end products, and environmental and genetic clues play an important role in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
128
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(144 citation statements)
references
References 89 publications
3
128
0
6
Order By: Relevance
“…In line with this, cohort studies, including prepubertal children with average diabetes duration of 5–8 years, revealed glomerular base membrane thickening and mesangial expansion [16], while they also disclosed that long-standing nonalbuminuric T1D participants might have significant glomerulopathy lesions [1719, 21]. Moreover, the prevalence of nonalbuminuric CKD in T1D was recently reported to be 2% and was associated with a higher risk of cardiovascular morbidity as well as all-cause mortality in people with T1D [4, 5]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, cohort studies, including prepubertal children with average diabetes duration of 5–8 years, revealed glomerular base membrane thickening and mesangial expansion [16], while they also disclosed that long-standing nonalbuminuric T1D participants might have significant glomerulopathy lesions [1719, 21]. Moreover, the prevalence of nonalbuminuric CKD in T1D was recently reported to be 2% and was associated with a higher risk of cardiovascular morbidity as well as all-cause mortality in people with T1D [4, 5]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, it represents a significant burden to the patients and the society they live in [2, 3]. Moreover, nonalbuminuric DN has been reported to have a prevalence of 2% among people with T1D and chronic kidney disease (CKD) [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, clinical application of novel hypoglycaemic drugs such as daglitazine, a sodium‐glucose cotransporter‐2 (SGLT2) inhibitor, can increase urinary glucose excretion, control blood sugar and reduce glomerular injury, thereby delaying the deterioration of renal function in DKD. Nektaria found that there are many common signalling pathways between TECs and GECs, in which crosstalk plays a vast role (Figure ) . During the occurrence of DKD, abnormal secretion of vascular endothelial growth factor (VEGF), angiopoietin‐1 (Ang‐1) and inflammatory factors and hypoxia promotes injury to GECs.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of DN can be explained by the upregulation of angiotensin II (Ang II) receptors in efferent arterioles that are induced by hyperglycemia, with subsequent increases in the sensitivity to Ang II. Efferent arteriolar vasoconstriction leads to increased hydrostatic glomerular capillary pressure, hyperperfusion, hyperfiltration, and microalbuminuria (Papadopoulou‐Marketou, Chrousos, & Kanaka‐Gantenbein, ).…”
Section: Discussionmentioning
confidence: 99%